HIV and an Ageing Population—What Are the Medical, Psychosocial, and Palliative Care Challenges in Healthcare Provisions - Mohamed H. Ahmed; Fatima Ahmed; Abu-Bakr Abu-Median; Maria Panourgia; Henry Owles; Bertha Ochieng; Hassan Ahamed; Jane Wale; Benjamin Dietsch; Dushyant Mital (Microorganisms, 2023)
The continuing increase in patient numbers and improvement in healthcare provisions of HIV services in the UK, alongside the effectiveness of combined antiretroviral therapy (cART), has resulted in increasing numbers of the ageing population among people living with HIV (PLWH). It is expected that geriatricians will need to deal with many older people living with HIV (OPLWH) as life expectancy increases. Therefore, geriatric syndromes in OPLWH will be similar to the normal population, such as falls, cognitive decline, frailty, dementia, hypertension, diabetes and polypharmacy. The increase in the long-term use of cART, diabetes, dyslipidaemia and hypertension may lead to high prevalence of cardiovascular disease (CVD). The treatment of such conditions may lead to polypharmacy and may increase the risk of cART drug–drug interactions. In addition, the risk of developing infection and cancer is high. OPLWH may develop an early onset of low bone mineral density (BMD), osteoporosis and fractures. In this review, we have also provided potential psychosocial aspects of an ageing population with HIV, addressing issues such as depression, stigma, isolation and the need for comprehensive medical and psychosocial care through an interdisciplinary team in a hospital or community setting. OPLWH have a relatively high burden of physical, psychological, and spiritual needs and social difficulties, which require palliative care. The holistic type of palliative care that will improve physical, emotional and psychological wellbeing is discussed in this review.